Utilization of harvested rainwater for ensuring green-fodder availability in arid Rajasthan - KUMAWAT, R N; PATIDAR, M; MATHUR, B K; SANTRA, P (The Indian Journal of Agricultural Sciences, 2022)
The efficient use and management of natural resources are important factors for success in agricultural farming. An experiment was conducted on round the year fodder production at ICAR-Central Arid Zone Research Institute, Jodhpur, Rajasthan during 2017–18 to 2019–20 by harvesting rainwater from the rooftop of buildings and irrigating crops using a solar operated water pump though drips and micro-sprinklers for efficient use of harvested water. In the 3 m inter-row spaces of bajra napier hybrid (BNH) variety CO 4, three legumes Vigna unguiculata (cowpea), Clitoria ternatea (butterfly pea) and Lablab purpureus (sem) received 40 and 60 kg P/ha, grown as intercrops during the rainy (kharif) season and lucerne in succession on residual P during winter (rabi) season. Among three kharif legumes, significantly higher green (11.19 t/ha) and dry (1.60 t/ha) fodder yields were recorded with cowpea that received 60 kg P/ha. An average 243.97 t/ha green and 37.55 t/ha dry fodder yields was recorded from the system in which share of BNH in green and dry fodder yield was 67.57 and 61.81% respectively. BNH gave 164.85 and 23.21 t/ha green and dry fodder from six cuts, kharif legumes contributed 7.43 t/ha in the green fodder and 1.12 t/ha in dry fodder from a single cut and lucerne produced 71.53 t/ha green and 10.32 t/ha dry fodder from the seven cuts in a year. This system has the capacity to meet out the green fodder requirement of 4–5 adult cattle unit (ACU) round the year from the land unit of 0.1 ha.